Compliance without Ratification. Using International Law in Non-Binding Scenarios - Friedman, Andrew (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2021)
While the end goal of international treaties is full participation, states are often resistant to ratification. As such, it is worthwhile to examine the effects that international law, including international treaties, have on states prior to ratification. This paper endeavors to determine the extent to which non-state-parties utilize international legal instruments, including the ways in which such law is included in domestic legal regimes and by looking at case studies where international law, used as a proxy for “rejoining the international community” has played a significant role in policy making despite a lack of ratification. The paper also examines the pushback on this framing and potential negatives. By examining the effects of international law on non-state-parties it opens up new forms of advocacy based on international legal norms and instruments, even in states that have not ratified such instruments in conjunction with advocacy efforts on ratification.